2004
DOI: 10.1111/j.0013-8703.2004.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory response of two aphid parasitoids, Lysiphlebus testaceipes and Aphidius colemani, to aphid‐infested plants from a distance

Abstract: The role of volatile stimuli in the host-searching behaviour of the two parasitoid species Lysiphlebus testaceipes Cresson and Aphidius colemani Viereck (Hymenoptera: Braconidae) was studied in relation to the host Aphis gossypii Glover (Homoptera: Aphididae) on cucumber plants, Cucumis sativa L. (Cucurbitaceae). Experiments were carried out in the laboratory in a wind tunnel, exposing individual parasitoids to signals from three sources simultaneously: (1) a complex of cucumber plants, Cucumis sativa, and A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 39 publications
0
24
0
3
Order By: Relevance
“…Other important factor is that the L. testaceipes parasitoid species, in particular, showed a low capacity to locate the host, since it has a limited response to volatiles released by the plants (Lo Pinto et al 2004, Fauvergue et al, 2006. Therefore, this species in a plant with no wheat aphids may be captured owing to theirs disorientation or during transit, while they searched for hosts in other crops.…”
Section: Discussionmentioning
confidence: 99%
“…Other important factor is that the L. testaceipes parasitoid species, in particular, showed a low capacity to locate the host, since it has a limited response to volatiles released by the plants (Lo Pinto et al 2004, Fauvergue et al, 2006. Therefore, this species in a plant with no wheat aphids may be captured owing to theirs disorientation or during transit, while they searched for hosts in other crops.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this study shows that the flight capacity of P. volucre remains high, even after 20 days of storage at 5°C. Although the flight behaviour of Aphidiinae parasitoids has been studied (Guerrieri et al, 1993(Guerrieri et al, , 1999Lo Pinto et al, 2004) and their flight capacity at low temperature determined (Langer et al…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several braconid aphid parasitoid species have been reported as responding to a variety of olfactory cues linked with the host or with the host's habitat (Jang et al 2000;Carver and Franzmann 2001). Pinto et al (2004) showed that the two parasitoid species Lysiphlebus testaceipes and Aphidius colemani (Hymenoptera: Braconidae) responded to stimuli from the host plants of A. gossypii in a similar way to parasitoids of aphid pests in other crops. Also, Silva et al (2007) showed that Doryctobracon areolatus and D. longicaudata females responded to the odors of uninfested rotting guavas, although D. areolatus was also attracted to fruits at the initial maturation stage.…”
Section: B Oleraceamentioning
confidence: 99%